Snowball Throwing Learning Model : Increase Student Activity And Learning Outcomes - Kartika Manalu; Efrida Pima Sari Tambunan; Oki Permata Sari (Journal of Education and Teaching Learning, 2022)
This study aims to describe the snowball throwing learning model to increase student activity and learning outcomes. In this study, the method used was an experimental type using a quasi-experimental approach. Data collection techniques with the help of questionnaires, tests and documentation. To test the data analysis using the normality test, homogeneity test and hypothesis testing. The results of the study showed that there was a stimulus to student learning activity that was influenced by the Snowball Throwing learning model. It was indicated by an increase in the active category of 65.6%. Active learning using the Snowball Throwing model Also shows the very active category in the experimental class with a percentage of 95.6%. Learning with the Snowball Throwing method also affects the value of learning outcomes, there is an increase in the value from the category that does not meet the KKM score to a good category in meeting the KKM score. Based on the t-test obtained with a value of 7.424 > t-table 2.001, it shows that the Snowball Throwing learning model has contributed to the effectiveness and learning outcomes of students in class VIII Mts 1 PAB Helvetia, Deli Serdang Regency.